Informasi Dan Teknologi Dalam Perspektif Pendidikan Islam - Dedi S; Suriadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The presence of educational technology is a necessity to overcome the problems of education in remote-lagging regions. Although initially only expected to be able to